KOMUNITAS TUMBUHAN BAWAH PADA 2 TIPE HUTAN DI TAMAN NASIONAL LORE LINDU - Ramadhanil Ramadhanil (Universitas Tadulako, 2007)
The research about the understorey plant community in the Lore Lindu National Park Central Sulawesi has been conductedfrom March 2004 to February 2005. The research used multiple plots by survey methods with plot size 2X2 m as much 25 plots eachforest type. There were 2 types of observed forest namely: “wana” (primary forest) and “pangale” (primary disturbed forest). Theresult showed the understorey plant composition was differ in two forest types observed. “Wana” were dominated by Pilea wightii(Urticaceae), Curculigo orchimoides (Hypoxidaceae), Chionanthus ramiflorus (Oleaceae) Callophyllum soulatri (Clusiaceae)whereas “pangale” were dominated by Diplazium angustippina, Zizhipus sp (Rhamnaceae), Freycinetia angustifolia, Castanopsisaccuminatissima. The Shanon diversity index of wana (3.25) was higher than pangale (3.06).Keywords : Understorey plant, diversity, and Lore Lindu.